TRANSFORMASI DIGITAL DAN KINERJA INDUSTRI MEDIA DI INDONESIA - Marwah, Maulana Arie (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The purpose of this study is to (1) understand the characteristics of digitalization in media companies against the metrics used to calibrate performance, (2) find out the influence of digitalization on pre-digital adult media companies and new digital media in the growth of company revenue to company performance through efficiency ratios. Researchers expanded the analysis by looking at the differences in influence between new digital media companies and pre-digital adult media companies in this relationship and using a sample of 5 media companies including Netflix, Alphabet(YouTube), Media Nusantara Citra, Surya Citra Media, and Visi Media Asia. Researchers found the characteristics of digitalization that existed in each company that had a correlation with the performance of media companies in both groups, namely new digital media and pre-digital adult media. In addition, researchers performed a log linear regression of the company’s revenue receipts during the time the company maintained its digitization characteristics. The findings of this study may be relevant for media companies and academic research.